2013
DOI: 10.1016/j.jvs.2012.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Risk scoring system to predict 3-year survival in patients treated for asymptomatic carotid stenosis

Abstract: This easy predictive score underscores the association of medical risk factors with decreased 3-year survival. This finding may impact future clinical decisions for management of asymptomatic carotid disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 20 publications
(15 reference statements)
0
24
0
Order By: Relevance
“…The reason for validating these scores to predict long-term events is that many of the risk factors included (diabetes mellitus, chronic renal insufficiency, contralateral carotid stenosis, atrial fibrillation, congestive heart failure, and history of AMI) have been previously described as predictors of late cerebrovascular events, and have been associated to a lower long-term survival. 7,11,12,17,21 It is also interesting to use one single tool to stratify patients with high risk at short and long term, promoting measures of secondary cardiovascular prevention, which are more aggressive and personalized. To identify risk, subgroups are clinically relevant, because it has been demonstrated that patient awareness of their specific level of cardiovascular risk is a motivational factor for making lifestyle changes, and achieving a higher treatment compliance.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for validating these scores to predict long-term events is that many of the risk factors included (diabetes mellitus, chronic renal insufficiency, contralateral carotid stenosis, atrial fibrillation, congestive heart failure, and history of AMI) have been previously described as predictors of late cerebrovascular events, and have been associated to a lower long-term survival. 7,11,12,17,21 It is also interesting to use one single tool to stratify patients with high risk at short and long term, promoting measures of secondary cardiovascular prevention, which are more aggressive and personalized. To identify risk, subgroups are clinically relevant, because it has been demonstrated that patient awareness of their specific level of cardiovascular risk is a motivational factor for making lifestyle changes, and achieving a higher treatment compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Alcocer et al 24 identified DM, coronary intervention, COPD, chronic kidney disease (CKD), and age older than 80 years as predictive factors of poor survival and assigned them a score based on the HR associated with each. Setting a single cutoff at 2 points, they defined only two categories.…”
Section: Discussionmentioning
confidence: 99%
“…The score ≤2 predicted a 6.0% 3-year mortality, whereas score >2 was associated with a 31.6% 3-year mortality. [14] Age of >70 years had more atherosclerosis and comorbidities, with a frequent occurrence of coronary disease or stroke. Patients with congestive heart failure have poor cardiac function and increased embolism formation.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Some models have also been constructed with categorical scores for mortality prediction. [13,14] These have been made clear the risk of CAS in short-term events and mortality before procedure in individual patients, and the appropriate patients need to be selected to reduce MACE.…”
Section: Introductionmentioning
confidence: 99%